Civil society engagement and education for sustainable development (ESD) in Egypt: A case study of El-Warraq area - Shaheen, Heba (AUC Knowledge Fountain, 2012)
This study examined the level of civil society engagement in an initiative implemented in an area in Egypt called El-Warraq. The main objective of the initiative was to promote ESD through a summer educational and recreational program using hands-on activities that bring key sustainable development concepts to school students. The main objective of this research was to examine a framework for implementing ESD in schools in Egypt. The target population in this study was EL-Warraq community. The sample used for investigation was one of the public schools chosen for the EduCamp II pilot implementation, El-Saddat School. This research was based on qualitative data collection and analysis to answer the following questions: a) What are the main characteristics of ESD curricula and teachers training programs? b) Who are the stakeholders involved in ESD initiatives in Egypt? And what is the role of each stakeholder? c) Within El-Warraq context, how did the participants in this project perceive the collaboration and engagement among stakeholders? To what extent did the community engage in the project's activities? The study emphasized the need for a participatory approach in the framework of implementing ESD in Egypt, where all stakeholders are actively engaged and have equal sense of ownership, for more sustainable initiatives.